GAMIFICATION IN EDUCATION: EXPLORING ITS IMPACT ON MOTIVATION, ENGAGEMENT, AND COGNITIVE DEVELOPMENT IN LANGUAGE LEARNING (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This study explores the use of gamification in education, focusing on its impact on motivation, engagement, and cognitive development, particularly in language learning. By integrating game elements such as rewards, challenges, and competition into educational settings, gamification enhances both intrinsic and extrinsic motivation. The article reviews the benefits of gamified learning, including improved memory retention and problem-solving skills, while also addressing criticisms about over-reliance on extrinsic rewards. The findings contribute to the growing body of literature on effective pedagogical strategies for modern education.